A protective factor against lymph node metastasis of papillary thyroid cancer: Female gender. Issue 3 (June 2023) - Shi, Ping; Yang, Dongqiang; Liu, Yan; Zhao, Zhijun; Song, Junjian; Shi, Huijing; Wu, Yanzhao; Jing, Shanghua
Abstract: Objective: Papillary thyroid carcinoma (PTC) is the most common pathological type of thyroid cancer, with good prognosis, but the rate of lymph node metastasis (LNM) is high, and the difference between men and women is significant. Therefore, the related risk factors for LNM of PTC based on gender were examined in this study in order to draw attention to gender factor in PTC. Methods: We retrospectively analyzed the clinicopathological data of 2103 patients with surgically confirmed PTC at the Fourth affiliated Hospital of Hebei Medical University West Side between January 2016 and December 2019. Results: LNM was detected in 1124 of the 2103 cases of PTC. Logistic regression analysis showed that LNM was associated with age ( p < 0.001, OR:0.547), gender ( p < 0.001, OR:2.609), tumor diameter ( p < 0.001, OR:2.995), bilaterality ( p =0.003, OR:1.683), and extrathyroid extension ( p < 0.001, OR:1.657). After propensity score matching, female gender ( p < 0.001, OR: 0.393) remained an independent factor of LNM in patients with PTC. LNM in men was only associated with diameter ( p < 0.001, OR: 3.246). LNM in woman was associated with menopausal history ( p = 0.012, OR=0.684), reproductive history ( p < 0.001, OR=0.360), abortion history ( p = 0.011, OR=0.725), tumor diameter >1 cm ( p < 0.001, OR=2.807), bilaterality ( p =0.006, OR:1.728), and extrathyroid extension ( p < 0.001, OR=1.879). Conclusion: Although the invasion is high in female patients, the rate of LNM is significantly reduced due to the influence of sex hormones and reproductive factors. For female patients of childbearing age who were not pregnant and did not have children, it is suggested to take a positive attitude towards their lymph nodes.